43y=3-x

The standard form of a linear equation is Ax+By=C.

Multiply both sides by 3.

3(43y)=3(3-x)

Combine 43 and y.

34y3=3(3-x)

Cancel the common factor of 3.

Cancel the common factor.

34y3=3(3-x)

Rewrite the expression.

4y=3(3-x)

4y=3(3-x)

4y=3(3-x)

Apply the distributive property.

4y=3⋅3+3(-x)

Multiply.

Multiply 3 by 3.

4y=9+3(-x)

Multiply -1 by 3.

4y=9-3x

4y=9-3x

4y=9-3x

Add 3x to both sides of the equation.

4y+3x=9

Reorder 4y and 3x.

3x+4y=9

3x+4y=9

Rewrite in Standard Form 4/3y=3-x